Strategies for Clarifying Penicillin Allergies When Skin Testing Is Not an Option - Elizabeth W. Covington; Mary Joyce B. Wingler; Rebecca A. Jayakumar; C. Whitney White (MDPI AG, 2019)
Patients with reported penicillin allergies have been proven to experience negative health consequences, such as increased cost, suboptimal antimicrobial therapy, and adverse reactions. Though skin testing has been proposed as a method to clarify penicillin allergies, many institutions may lack the resources to perform skin testing on a wide scale. This literature review describes the current literature surrounding the use of penicillin allergy interviews when skin testing is not an option. Specifically, the review highlights the steps in carrying out a successful antibiotic allergy patient interview, summarizes the clinical evidence surrounding antibiotic allergy clarifications, and addresses key advantages and disadvantages of clarifying antibiotic allergies without the availability of skin testing.